2023
DOI: 10.3390/cells12081128
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Ferroptosis and Updates of Ferroptosis Studies in Cancers and Leukemia

Abstract: Ferroptosis is a mode of cell death regulated by iron-dependent lipid peroxidation. Growing evidence suggests ferroptosis induction as a novel anti-cancer modality that could potentially overcome therapy resistance in cancers. The molecular mechanisms involved in the regulation of ferroptosis are complex and highly dependent on context. Therefore, a comprehensive understanding of its execution and protection machinery in each tumor type is necessary for the implementation of this unique cell death mode to targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 216 publications
0
10
0
Order By: Relevance
“…Ferroptosis, a recently discovered controlled cell death program, is triggered through iron-dependent lipid peroxidation and represents a distinct type of cell death compared to other well-known forms[6, 30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, a recently discovered controlled cell death program, is triggered through iron-dependent lipid peroxidation and represents a distinct type of cell death compared to other well-known forms[6, 30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent discoveries in iron metabolism and the newly discovered process of ferroptosis have opened up new possibilities in the field of anticancer therapies [ 17 ]. Therefore, targeting ferroptosis could provide new insights into leukemia treatment strategies [ 81 , 82 ].…”
Section: Promoting Ferroptosis As a Novel Leukemia Treatment Strategymentioning
confidence: 99%
“…Imetelstat, a novel telomerase inhibitor currently being tested in a phase 2 clinical trial for AML (NCT05583552), has been shown to stimulate the synthesis of phospholipids containing polyunsaturated fatty acids (PUFAs) in an ACSL4- and FADS2-dependent manner, leading to ferroptosis in AML cells both in vitro and in vivo [ 218 ]. However, it remains unclear whether the induced ferroptosis is a result of telomerase inhibition or off-target effects of the drug [ 82 ].…”
Section: Promoting Ferroptosis As a Novel Leukemia Treatment Strategymentioning
confidence: 99%
“… 39 , 40 The term “Ferroptosis” was coined by Dixon et al in 2012 to describe a specific type of cell death that occurs due to the accumulation of iron and lipid reactive oxygen species. 41 , 42 …”
Section: Ferroptosis and Its Processmentioning
confidence: 99%